O ensino de ciências na concepção dos alunos - Rodrigues, Eva Solange Gonçalves (Universidade Federal do Tocantins, 2021)
This study aimed to analyze the teaching of science, based on the student's opinion about the way the lessons are being taught . The survey was conducted with students of the 6th year of the State School Marshal Artur da Costa e Silva and State School Dom Pedro I, in the city of Porto Nacional, Tocantins, in agreement with the direction of both schools . The interviews were conducted between January and February this year . Students from both schools had the opportunity to meet relevant classes ciências.As objective questions were analyzed and plotted on the table and the discursive were cited over the results and discussions and open-ended questions. In order to analyze a greater number of issues, eighty (80 ) questionnaires were applied to both schools , classes in the morning and afternoon. Since the objective questions included questions on the survey of prior knowledge and student participation in science class , the discursive treated - is about the same opinion with respect to those classes .